Pelatihan dan Sosialisasi Kesadaran Limbah Fast Fashion pada Santri Madrasa Mahasiswa Muamalat Yogyakarta: Indonesia - Rohma, Masitoh Nur; Priyansyah, Ahmad; Irmawati, Feni; Maghfiroh, Maghfiroh; Nihaya, Silvia Munna (Jurnal Abdimas Madani dan Lestari (JAMALI), 2024)
Based on United Nations data, the fashion industry contributes as much as 10% to total global emissions. This condition negatively contributes to climate change, especially when associated with Sustainable Development Goals (SDGs) Point 13, climate action. In response to this condition, the community service team from the Department of International Relations, Universitas Islam Indonesia, strives to open opportunities for the implementation of SDGs Point 13 at the Madrasa Mahasiswa Muamalat, Yogyakarta. The method of activity is carried out face-to-face by conducting socialization and providing training to the santri. The first session was a socialization of "Implementation of Sustainable Development Goals Point 13: Fast Fashion Trends," while the second session was "Training of How to Transform Fashion Waste into Bags". This community service activity is aimed at supporting the achievement of targets in SDGs Point 13, namely increasing education, awareness, and the capacity of human and institutional resources about mitigation, adaptation, impact reduction, and early warning of climate change. Operationally, this service activity aims to increase awareness of fast fashion waste and the capacity of santri in mitigation and adaptation to climate change. The result of this activity is that the santri experienced an increase in insight regarding fast fashion and climate change, and the santri have the capacity to make bags from fast fashion waste.